Positive psychology and virtue: Values in action. Issue 1 (2nd January 2019) - Stichter, Matt; Saunders, Leland
ABSTRACT: This paper provides an overview of the issues and themes that were discussed on an interdisciplinary panel which occurred at the American Philosophical Association's pacific division meeting in April of 2017. The panel focused on the connections between the VIA classification of virtues and character strengths in psychology and virtues and the Aristotelian approach to virtue in philosophy. Three key themes emerged from the papers presented at this panel: 1) the nature of the relationship between virtues and character strengths on the VIA model; 2) the extent to which the conceptions of virtues and character strengths are best understood as universal or culturally-embedded; and 3) the reliability of using self-report measurements to measure character strengths. This paper serves to frame papers that resulted from that panel and were incorporated into this special issue of the Journal of Positive Psychology.